The symmetries of McCullough-Miller space - Piggott, A. (Algebra and Discrete Mathematics, 2012)
We prove that if W is the free product of at least four groups of order 2, then the automorphism group of the McCullough-Miller space corresponding to W is isomorphic to group of outer automorphisms of W. We also prove that, for each integer n ≥ 3, the automorphism group of the hypertree complex of rank n is isomorphic to the symmetric group of rank n.